Enhanced methanol electro-oxidation activity of CuO nanoparticles derived from the thermal decomposition of a CuII salophen type coordination compound - Zohreh Shaghaghi; Rahman Bikas; Mehri Aligholivand; Sahar Jafari; Vasyl Kinzhybalo (Scientific Reports, 2025)
Abstract Electrocatalysts based on Cu compounds have been considered as a suitable alternative to platinum compounds due to their low cost, high abundance, excellent redox properties, and performing the methanol oxidation reaction (MOR) at low potentials. This article represents a study of CuO nanoparticles (NPs) prepared through a simple method of thermal decomposition of the CuL coordination compound (H2L = N,N′-bis(salicylidene)-4-chloro-1,2-diaminobenzene), C20H13ClCuN2O2, as a precursor by different electrochemical methods. A comparison of the MOR ability of precursor (CuL) and CuO NPs shows that both compounds are active, but CuO NPs present a peak current density of about 248 mA cm− 2 when screened for catalytic MOR in 1.0 M KOH with 0.5 M methanol, which is superior to the performance of CuL and some previously reported related catalysts based on CuO. The methanol oxidation peak at 0.69 V vs. Ag/AgCl is also more intense than CuL (0.77 V). The modified electrode with CuO NPs also shows lower onset potential, lower Tafel slope, higher electrochemically active surface area (ECSA) and better stability compared to the CuL electrode. These advantages can be assigned to the higher activity of catalytic sites and the lower charge transfer resistance of CuO due to its higher electrical conductivity than the CuL.